Belief in conspiracy theories about COVID-19 vaccines among Brazilians - Camargo, Emerson Lucas Silva (2024)
Funding Information: Coordena\u00E7\u00E3o de Aperfei\u00E7oamento de Pessoal de N\u00EDvel Superior\u2014CAPES\u2014Grant Number: 001/2023. Publisher Copyright: © 2024 by the authors.